Potensi Ekonomi Kendal Sebagai Daerah Penyangga Ibukota Provinsi Jawa Tengah - Pribadi, Yanuar (Journal of Management Review, 2023)
This study aims to reveal the economic development of Kendal Regency, Central Java Province based on the lead economic sector in 2016-2022. Kendal Regency is a buffer zone for the capital of Central Java Province with a fairly high poverty rate and a very low regional fiscal capacity. This research used descriptive quantitative analysis through statistical data publication using Location Quotient and Dynamic Location Quotient methods. The results showed that there were limited prospective economic sectors in the Kendal Regency. It shows that the economic development in Kendal Regency has not been in a positive direction because of the lack of sectors that become economic strength in the Kendal Regency. Local governments ought to make changes immediately to improve the welfare of the local community by encouraging the development of sectors with the right policies.